Things fall apart containing the spillover from an Iraqi civil war - Byman, Daniel, 1967- (Brookings Institution Press, 2007)
"Studies the history of recent civil wars to derive lessons regarding the impact of full-scale civil wars on the security, prosperity, and national interests of other states. Proposes recommendations for the United States as it confronts the possibility of a similar conflict in Iraq and its spillover into the region"--Provided by publisher.